Strategi Rumah Zakat Dalam Meningkatkan Kesejahteraan Masyarakat di Sumatera Utara - Pohan, Novita Sari; Siregar, Saparuddin; Rahma, Tri Inda Fadhila (ITB AAS INDONESIA Surakarta, 2024)
This research aims to find out the main priority strategy for Rumah Zakat in improving the welfare of the people in North Sumatra. by presenting the internal and external conditions that have been carried out so far. Then, in addition, the researcher also explained several urgent measures that need to be implemented so that the Zakat House can be more focused. The method used is a qualitative method using SWOT and QSPM analysis. The number of respondents who filled out the questionnaire were 5 respondents each for SWOT and 5 respondents for QSPM. Based on the results of the SWOT analysis, the strategy quadrant obtained after processing it in the IFE and EFE matrices is in Quadrant I. This states that the strategy used is a progressive strategy. This strategy means that the company has strengths and opportunities. Furthermore, the QSPM analysis showed that the main priority strategy that must be implemented is encouraging and adopting the use of information technology to create efficient and effective Zakat governance.